Giant Intramuscular Lipoma of the Gluteus: A Case Report and Literature Review (Journal of Analytical Oncology, 2024)
Lipomas are benign tumors of mesodermal origin composed of mature adipocytes. They are classified into superficial and deep types located in the subcutaneous and subfascial locations respectively. The subfascial is further subdivided into 2 subtypes intermuscular and intramuscular. Presented was a 63 year old woman with a right sided swelling of the buttock in the past 7 months. Clinical, imaging and histologic evaluation resulted in the definitive diagnosis of a giant intramuscular lipoma of the gluteus. The lesion was well circumscribed with a defined pseudo capsule an indication of a benign disease with minimal risk of recurrence when compared to the infiltrative type. Giant intramuscular lipoma should be considered as a differential diagnosis of a gluteal mass. CT scan was useful in the preoperative diagnosis that included the nature of the tumor due to the low attenuation of fat, homogenous echogenicity, well defined capsule that were in favour of a benign lesion than malignancy. This was in addition to the extent of the tumour. Surgical excision provided the definitive diagnosis.